Leprosy after the Elimination: A BPKIHS experience - S Bhattarai; S Agrawal; A Rijal; S Marahatta (Nepal Journal of Dermatology, Venereology & Leprology)
DOI: http://dx.doi.org/10.3126/njdvl.v11i1.7933